Can kinesio tape negatively affect the treatment by creating a hard floor in plantar fasciitis treatment? A randomized clinical trial - Tuğba Kocahan; Aydan Orscelik; Hüseyin Günaydın; Gokhan Buyukluoglu; Burak Karaaslan; Erdoğan Asar; Bihter Akınoğlu (PLoS ONE, 2025)
Background Radial extracorporeal shock wave therapy (r-ESWT) is accepted as one of the most effective treatment modalities for plantar fasciitis (PF). Also kinesio taping (KT) applicationis effective for the treatment of PF. However, there is not enough evidence about the effectiveness of the combination of these two modalities in the treatment of PF. This prospective randomized clinical trial was planned to investigate the acute effects of KT application in addition to r-ESWT application on pain, foot function and flexibility. Methods The study was performed on 42 patients with unilateral PF, that were randomly assigned into two groups receiving four sessions of either r-ESWT or r-ESWT+KT treatment once per week. All patients performed home exercises. Patients’ pain levels were evaluated via the Visual Analogue Scale (VAS), and foot function via the Foot Function Index (FFI). Flexibility was evaluated through gastro-soleus and plantar fascia flexibility tests. The evaluations were done before and one week after the final treatment. Two Way Analysis of Variance with Repeated Measures and Generalized Estimating Equations (GEE) methods were used in statistical analyses. Results As a result, rest pain and activity pain decreased in both groups and there is no differences between the groups (respectively p: 0,831; p: 0.331). FFI pain and disability subscores decreased and were also similar between the groups (respectively p: 0.304; p: 0.978). FFI activity limitation subscore decreased in the r-ESWT group more than r-ESWT+KT group (p: 0.002). Night pain, gastro-soleus and plantar fascia flexibility did not change in both goups (respectively p: 0.713; p: 0.413; p: 0.475). Conclusion Adding KT to r-ESWT application did not create an additional pain relieving effect, on the contrary, resulted in less improvement in activity limitation. This may be related to the fact that KT application to the sole and heel region creates a hard surface on the heel. r-ESWT application may be more beneficial in PF where activity limitation are prominent. ClinicalTrials.gov The registration number: NCT06516393